(untitled) (DAPesquisa, 2022)
This article analyzes a theatrical mediation practice developed with spectator-passers-by, invited to fill dialogue balloons with comic strips of the main characters of the play, configuring another space of experience. The material produced by the spectators, through drawing and writing, provided affective experiences, allowing them to objectively observe what caught the public’s attention and, eventually, what caused an impact.